AN APPRAISAL OF THE 21ST CENTURY THROUGH BAUDRILLARD'S IDEAS IN THE CONTEXT OF THE INTERPLAY AMONG POLITICS, PHILOSOPHY, ORGANIZATIONS AND BEING HUMAN - Onur Kazancı; Aytaç Odacılar (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This paper explores the relationship between philosophy and politics in the twenty-first century, using the thought of Jean Baudrillard, one of the most prominent intellectuals of the 20th century, taking into account the idea of what it means to be human. The study will argue that the human being is a creature capable of aestheticization as the capacity to express something with the help of other things. After setting forth such a definition of the human being as a basis, the study will then address the relationship between philosophy and politics. In this context, the historical foundations of this relationship will be presented within the framework of the study. Then, the state of philosophy-politics interaction in the twenty-first century will be discussed in the light of historical themes and Baudrillard's ideas. Finally, an evaluation of all the explanations will be made in relation to some of the problems that are visible today and potential approaches will be put forward to rectify the problems in this connection.